Pelvic inflammatory disease hospitalizations in Brazil: time trend from 2000 to 2019 - Patrick Perciney; Ana Luísa Soares Costa; Isabel Cristina Gonçalves Leite; Mário Círio Nogueira (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to evaluate the temporal trend of hospitalizations for pelvic infammatory disease in Brazil and its regions between 2000 and 2019. Methods: longitudinal ecological study with data from the Hospital Information System. The analysis of temporal trends in hospitalization rates by age group was performed using segmented linear regression (joinpoint regression). Both annual percent change total and by age groups were estimated for Brazil and each region. Results: Brazil had an average reduction of 5.2% per year in the period and the age groups most affected were 20 to 29 and 30 to 39 years. North region had the highest rates and South and Southeast regions, the lowest. Midwest region had the largest annual average reduction (8.1%), followed by the Northeast (5.7%), Southeast (5.0%), North (4.6%) and South (4.3 %). The only age group that showed a significant increase was that of 10 to 19 years in the Southeast in the period from 2008 to 2019 (0.9%) and in the Northeast in the period from 2014 to 2019 (3.3%). Conclusions: hospitalization due to pelvic infammatory disease has significantly decreased in Brazil. The increase observed for adolescents in the Southeast and Northeast in the most recent period points to problems in the prevention and control of sexually transmitted infections in this age group.